IV Taller Nacional sobre Cáncer Bucal: una fortaleza para la Estomatología Cubana - García Heredia, Gilda; Bécquer Aguila, Jorge Luis; Gispert Abreu, Estela de los Angeles (Revista Cubana de Estomatología, 2016)
Last December, he welcomed the holding of the "IV National Workshop on Oral Cancer", at the headquarters of the National Institute of Oncology and Radiobiology (INOR), located in the Havana neighborhood of Vedado. The Cuban Society of Stomatology has been organizing these meetings since 2012, inspired by the celebration of the Day of the fight against oral cancer in Latin America (December 5), instituted by the executive committee of the Latin American Odontological Federation (FOLA), on a proposal of the Federation of Argentina, in recognition of the work of the Professor of Merit J ulio César Santana Garay, founder of the Cuban program for the prevention of this disease, who is celebrating his birthday on that date of the last month of the year. On this occasion the inaugural words were pronounced by Dr. C. Estela Gispert Abreu, president of the Cuban Society of Stomatology. The event went through three important moments: • The first served to honor professors and professionals with a distinguished career in the prevention, diagnosis and treatment of oral cancer in our country: Julio César Santana Garay and Josefa Miranda Tarragó (founders of the Program for the Detection of Oral Cancer - PDCB), Iván Cuevas Pérez, Nélido González Fernández, José Ramón Díaz Martínez, Carlos Frómeta Neira, Pedro Pablo Morales Echeverría and Guillermo Sánchez Acuna, all prestigious Cuban professors and researchers. • In the second moment, a scientific session was held. Lectures were given with novel topics and updating. An example of these was "The diagnostic role of HPV and p16 in cancer of the oropharynx", taught by Dr. C. Maite Hernández Menéndez and the MCs. María de los Ángeles Ríos Hernández, Researchers of the Molecular Biology Group of the National Institute of Oncology and Radiobiology. Cancer is a health problem in developing countries and in immunosuppressed populations. It was known that one of every five cases of this disease in the world, is related to infections, mostly viral. Viruses have identifiable targets for diagnosis, prevention and therapy of oropharyngeal cancer. In addition to the "status" of HPV and the expression of p16, other biomarkers can be determined to know which subgroup of cancer of the head and neck is associated with HPV and responds better to treatment with chemotherapy or radiotherapy. This topic is new because of the scientific evidence for the stomatological community about the role of infection of the HPV virus in the oral cavity ─ which is related to sexual behavior, including the practice of oral sex─, so that actions can be designed of promotion and prevention of health with the population. Another of the topics discussed was "The stomatologist in the early diagnosis of lesions in the mesopharynx", presented by Professor Pedro Pablo Morales, Specialist in Otolaryngology, Head and Neck Service of INOR. It was important to recognize that mesopharyngeal cancer develops in an accessible anatomotopographical region; however, the fact that the survival rate is low is contradictory. Simply by performing a thorough examination of the oral complex ─ taking into account the clinical method and the knowledge of the signs and symptoms of alarm on the part of the professionals─, cancer can be detected in initial stages, and thus promote the increase in the rate of curability and survival. It was also known about the "Diagnosis and Therapeutics of Salivary Gland Neoplasms", excellently presented by the MCs Dr. Johannes Mestres Cabello, specialist in Maxillo-Facial Surgery of the Head and Neck Service of INOR. The statistical data were interesting, since they showed that malignant salivary gland neoplasms constitute less than 0.5% of all cancers and approximately between 3% and 5% of all cancers of the head and neck, more frequent in males, and more than 70% is located in major glands (most in parotid glands). Mucoepidermoid carcinoma is the malignant neoplasm found most frequently in salivary glands (10% of the total). The majority of patients with malignant salivary gland tumors are between 60 and 70 years of age. Although there are clinical features that distinguish malignant from benign tumors, the treatment is contradictory in some cases, so the new guide in the country for the diagnosis and treatment of salivary gland neoplasms, developed by the Head Service was exposed and Cuello del INOR, the country’s governing center. Equally interesting was the theme "Quality of life in primary caregivers of palliative patients with cancer of the head and neck", presented by the Professor and MCs Dr. Gilda García Heredia, Specialist in General Comprehensive Stomatology, Head and Neck Service of INOR.